Studi Konseptual Museum Negeri Sirisori Islam - Syahruddin Mansyur (Kapata Arkeologi, 2013)
Maluku provincial government has the local characteristic as represented in the “pemerintahan negeri” as a unified system of customary communities in Maluku province government areas. It gives an understanding that the land administration system has implications for aspects of customary law relevant to understanding the history of the culture of a country. Therefore, in the context of the preservation of cultural resources, land administration is the collective memory of the people of Maluku that must be preserved. In regard to the preservation of cultural resources, research conducted in the State Islamic Sirisori is expected to summarize the totality of the cultural history of the country Sirisori Islam. Further more, the results of this study is a conceptual study on the establishment of the museum Sirisori Islamic country. Based on the conceptual study, an alternative form of museum management can adapt the form of eco-museum as an attempt to preserve the cultural resources that existin Sirisori Islamic State. The themes that can be displayed in a museum presentation; State History Sirisori Islam, Islamic tradition Sirisori State Society, and the State Archaeological Collection Sirisori Islam.Provinsi Maluku memiliki karakteristik pemerintahan yaitu sistem Pemerintahan Negeri sebagai kesatuan masyarakat hukum adat dalam wilayah pemerintahan Provinsi Maluku. Hal ini memberi pemahaman bahwa sistem pemerintahan negeri memiliki implikasi pada aspek hukum adat yang terkait dengan pemahaman sejarah budaya suatu negeri. Oleh karena itu, dalam konteks pelestarian sumber daya budaya, pemerintahan negeri merupakan memori kolektif masyarakat Maluku yang harus dilestarikan. Dalam kaitan pelestarian sumberdaya budaya tersebut, penelitian yang dilakukan di Negeri Sirisori Islam ini diharapkan dapat merangkum totalitas sejarah budaya negeri Sirisori Islam. Selanjutnya, hasil penelitian ini  merupakan kajian konseptual pendirian museum negeri di Sirisori Islam. Berdasarkan kajian konseptual tersebut,  alternatif bentuk pengelolaan museum dapat mengadaptasi bentuk eco-museum  sebagai upaya untuk melestarikan sumberdaya budaya yang ada di Negeri Sirisori Islam. Tema-tema yang dapat ditampilkan dalam penyajian museum diataranya; Sejarah Negeri Sirisori Islam, Tradisi Masyarakat Negeri Sirisori Islam, dan Koleksi Arkeologi Negeri Sirisori Islam.